1,3-Dibenzoylimidazolidine-2-thione and 1,3-dibenzoyl-3,4,5,6-tetrahydropyrimidine-2(1H)-thione - Kazak, C; Yilmaz, VT; Servi, S; Koca, M; Heinemann, FW (Int Union Crystallography, 2005)
The title compounds, 1,3- dibenzoylimidazolidine- 2- thione, C17H14N2O2S, ( I), and 1,3- dibenzoyl- 3,4,5,6- tetrahydropyrimidine-2( 1H)- thione, C18H16N2O2S, ( II), were obtained from the reactions of imidazolidine- 2- thione and 1,4,5,6-tetrahydropyrimidine- 2- thiol, respectively, with benzoyl chloride. Compounds ( I) and ( II) contain, respectively, imidazolidinethione [ C = S = 1.6509 ( 14) angstrom] and pyrimidinethione [ C = S = 1.6918 ( 19) angstrom] moieties bonded to two benzoyl rings. The molecules of ( I) exhibit C-2 symmetry, the C S bond lying along the twofold rotation axis, while the molecules of ( II) have mirror symmetry ( C-s). The imidazolidine ring in ( I) is essentially planar, while the pyrimidine ring in ( II) adopts a boat conformation. Molecules of ( I) are linked by weak intermolecular C - H center dot center dot center dot O interactions, while molecules of ( II) are held together by van der Waals interactions.
Keywords: Heterocyclic Thiones; Crystal-Structure; Complexes; Ligands; Copper